Transverse-momentum and pseudorapidity distributions of charged hadrons in pp collisions at square root of s = 7 TeV. - Khachatryan V; Sirunyan AM; Tumasyan A; Adam W; Bergauer T; Dragicevic M; Erö J; Fabjan C; Friedl M; Frühwirth R; Ghete VM; Hammer J; et al. (AMER PHYSICAL SOC)
Charged-hadron transverse-momentum and pseudorapidity distributions in proton-proton collisions at square root of s = 7  TeV are measured with the inner tracking system of the CMS detector at the LHC. The charged-hadron yield is obtained by counting the number of reconstructed hits, hit pairs, and fully reconstructed charged-particle tracks. The combination of the three methods gives a charged-particle multiplicity per unit of pseudorapidity dN(ch)/dη|(|η|<0.5) = 5.78 ± 0.01(stat) ± 0.23(syst) for non-single-diffractive events, higher than predicted by commonly used models. The relative increase in charged-particle multiplicity from square root of s = 0.9 to 7 TeV is [66.1 ± 1.0(stat) ± 4.2(syst)]%. The mean transverse momentum is measured to be 0.545 ± 0.005(stat) ± 0.015(syst)  GeV/c. The results are compared with similar measurements at lower energies.
Keywords: Science & Technology; Physical Sciences; Physics, Multidisciplinary; Physics; PHYSICS, MULTIDISCIPLINARY; PARTICLES; ENERGIES; DEPENDENCE; 01 Mathematical Sciences; 02 Physical Sciences; 09 Engineering